A simple algorithmic approach using histology and immunohistochemistry for the current classification of adult diffuse glioma in a resource-limited set-up. Issue 4 (11th August 2017) - Rajeswarie, R T; Rao, Shilpa; Nandeesh, Bevinahalli N; Yasha, T Chickabasaviah; Santosh, Vani
Abstract : Aims: The WHO 2016 classification of diffuse gliomas combines histological and molecular parameters for diagnosis. However, in view of cost constraints for molecular testing, an economical working formula is essential to reach a meaningful diagnosis in a resource-limited setting. The aim of this study was to establish a practical algorithmic approach using histology and immunohistochemistry (IHC) in the classification of diffuse gliomas in such a set-up. Methods: Diffuse gliomas of WHO grade II and III diagnosed in our institute in the year 2016 were analysed for histological and IHC features, using the markers isocitrate dehydrogenase 1 (IDH1R132H) and α thalassemia/mental retardation syndrome X-linked gene (ATRX). Fluorescence in situ hybridisation (FISH) for 1p/19q co-deletion was performed when requested. Results: 449 diffuse gliomas (grades II/III) were included in the study. Integrating histology and IHC features, as per the WHO 2016 guidelines, we derived the following groups: Astrocytoma, IDH-mutant (A, IDH-mt, 37.2%); astrocytoma, not otherwise specified (A, NOS, 12.7%); oligoastrocytoma, NOS (OA, NOS, 4.5%); and oligodendroglioma, NOS (ODG, NOS, 45.6%). FISH was performed in a subset of ODG, NOS, OA, NOS and A, NOS gliomas. This revealed 1p/19q co-deletion in all cases of ODG, NOS, 15.8% of OA, NOS and 37.5% of A, NOS. Sequencing for rare IDH 1/2 mutations was not carried out in this study. Conclusion: In a resource-limited set-up, histology with IHC (IDH1(R132H) and ATRX) form the baseline to reasonably derive four histomolecular subgroups of diffuse glioma. Of these, we recommend, OA, NOS and IDH1(R132H)-non-mt ODG, NOS to be our priority for performing 1p/19q co-deletion studies in comparison to IDH-mt ODG, NOS, and it would not be mandatory for astrocytoma. Sequencing for rare IDH mutations is advised for A, NOS and OA, NOS groups, but not for the IDH1(R132H)-non-mutant diffuse gliomas with 1p/19q co-deletion.